Body height, weight, and Body Mass Index – magnitude and pace of secular changes in children and adolescents from Kraków (Poland) between 1983 and 2020. Issue 9 (2nd July 2022) - Kryst, Łukasz; Żegleń, Magdalena; Woronkowicz, Agnieszka; Kowal, Małgorzata
Abstract: Objective: The aim of this study was to analyze the occurrence and pace of secular trends regarding body height, weight, and Body Mass Index (BMI) among children and adolescents from Kraków (Poland) examined in 1983, 2000, 2010, and 2020. Methods: The study group consisted of 17 407 individuals (8650 girls and 8757 boys) aged 3–18 included in four cross‐sectional studies conducted in 1983, 2000, 2010, and 2020.Analyzed anthropometric characteristics included body height (measured according to Martin's technique, with an anthropometer) and body weight. BMI was calculated as follows: body weight (kg)/body height 2 (m). Results: Results of the current study suggest that there was a cessation of previously observed secular increase of the body height in the examined population in the recent decade. Additionally, secular changes regarding body height, body mass, and BMI occurred noticeably slower in the recent decade compared to the previous years. Conclusions: In conclusion, the rapid increase of body height in the years 1983–2000 and later secular increase of the body mass and BMI in 2000–2010 were probably associated mainly with significant socio‐economic progress of the country. On the other hand, deceleration of those trends in 2010–2020, especially in regards to body height, may be associated with reaching the maximum genetically attainable body height in the examined population.